Crisis impact on the diversity of financial portfolios: Evidence from European citizens - Dorothea Schäfer; Michael Stöckel; Henriette Weser (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Since the 2008 Lehman bankruptcy, it is clearly shown that global economic and financial crises present major challenges to private households, requiring from them, a high level of shock absorption capacity. According to the old adage, "Do not put all the eggs in one basket", resilience depends, to a large extent on financial diversification. So far, especially for Europe, little is known about whether and how the Great Financial Crisis (GFC) affected the diversity of private households' investment portfolios. We tackle this research gap and explore the impact of the GFC on portfolio diversity of European private households. Our European focus complements Sierminska and Silber (2019) who explore the diversification behaviour of US households after the Lehman insolvency. Our study reveals a significant decrease in the diversity of financial portfolios. This finding is robust across distinct model specifications. In response to the GFC, evidence suggests that European households adjusted the diversity of their financial portfolio in the opposite directions to that of US households.
Keywords: D14; G11; G01; G40; 330; financial and economic crisis; household finance; portfolio diversification; Shannon entropyindex; Gini-Simpson diversity index; background risk; risk aversion